Standar Isi, Bahasa, dan Penyajian Buku Tematik Terbitan Mediatama Tema 8 Daerah Tempat Tinggalku Seri HOTS - Mulyadi Setiawan; Sudirman; Muhammad Tahir (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
This study aims to analyze the contents of the thematic textbook published by Mediatama with the theme 8 Regions of Residenceju, HOTS series, grade IV Curriculum 2013. This study uses a qualitative approach. Methods of data collection using a study of documentation, the analysis begin with reading and reviewing all available data. The results of this analysis indicate that the thematic textbook published by Mediatama theme 8 My Living Area HOTS series class IV Curriculum 2013 in terms of the feasibility of content, language, and presentation is in accordance with the standards set by BSNP. However, there are still some shortcomings in terms of content, language, and presentation in terms of content, there are some deficiencies in the material that supports the achievement of KI and KD, and some learning does not contain any of the dimensions of factual, conceptual, and procedural knowledge. In terms of language, there are several shortcomings in the language used that are not in accordance with the rules of Indonesian and EYD, and the delivery of messages between sentences in paragraphs is not related. Meanwhile, in terms of presentation, there are indexes and glossaries that contain important terms in the text, which are not accompanied by explanations of these terms. In conclusion, the appropriateness of the content, language, and presentation contained in this book has met the standards set by BSNP.